Universal influenza virus vaccines and therapeutics: where do we stand with influenza B virus?. (August 2018) - Tan, Jessica; Asthagiri Arunkumar, Guha; Krammer, Florian
Highlights: Conserved epitopes on influenza B virus HA head, HA stalk, and NA exist. Broadly protective antibodies that target these epitopes have been isolated and might be developed into novel therapeutics. Very little work has focused on the development of broadly protective influenza B virus vaccines so far. Abstract : The development of a broadly protective or universal influenza virus vaccine is currently a public health priority worldwide. The vast majority of these efforts is exclusively focused on influenza A viruses. While influenza A viruses cause the majority of all influenza cases worldwide, influenza B viruses should not be ignored. Approximately 25% of all influenza cases are caused by influenza B viruses which circulate as two distinct B/Victoria/2/87-like and B/Yamagata/16/88-like lineages. In contrast to popular belief, influenza B cases frequently cause significant morbidity and mortality, especially in children. Similar to influenza A viruses, influenza B viruses drift antigenically and the influenza B components of current vaccines have to be reformulated almost on an annual basis. A broadly protective vaccine against influenza B viruses is therefore urgently needed. Here we review both broadly protective anti-influenza B antibodies as well as the sparse attempts to create a universal influenza B virus vaccine.